Hand eczema severity and quality of life: a cross-sectional, multicentre study of hand eczema patients. - Agner, T (2009)
BACKGROUND AND OBJECTIVES: Hand eczema is a chronic disease with negative impact on quality of life (QoL). In this study, QoL in hand eczema patients is assessed and related to age, sex, severity, and diagnostic subgroups. METHODS: A total of 416 patients with hand eczema from 10 European patch test clinics participated in the study. Data on QoL were obtained from a self-administered questionnaire using the Dermatology Life Quality Index (DLQI). Severity was assessed by a scoring system (Hand Eczema Severity Index, HECSI) as well as frequency of eruptions and sick leave due to hand eczema. RESULTS: No significant difference was found between males and females with respect to QoL [DLQI median values and 25/75 percentiles for males and females being 7.0 (3-14) and 8.0 (3-13), respectively], although males were more severely affected than females (P < 0.025). A significant positive correlation was found for hand eczema severity and age (P < 0.001), while no significant correlation was found for QoL and age. QoL was found increasingly reduced when sick leave was getting higher (P < 0.001). A statistically significant correlation between QoL (as measured by DLQI) and hand eczema severity as measured by HECSI was found (P < 0.001). No significant difference in QoL was found between diagnostic subgroups. CONCLUSIONS: QoL was found markedly negatively affected in hand eczema patients and was significantly correlated to disease severity. No significant difference in QoL was found between males and females, in spite of significantly more severe eczema in males, indicating that QoL in female patients is more easily affected.